Accumulation of childhood adversities and type 1 diabetes risk: a register-based cohort study of all children born in Denmark between 1980 and 2015. (2nd October 2020) - Bengtsson, Jessica; Byberg, Stine; Carstensen, Bendix; De Stavola, Bianca L; Svensson, Jannet; Jørgensen, Marit E; Rod, Naja H
Abstract: Background: Previous studies have indicated an association between childhood adversities and type 1 diabetes but have been underpowered and limited by selection. We aim to quantify the effect of accumulation of childhood adversities on type 1 diabetes risk, and to assess whether the effect differs between males and females in a large and unselected population sample. Methods: We used register-based data covering all children born in Denmark between 1980 and 2015, totalling >2 million children. We specified a multi-state model to quantify the effect of accumulation of childhood adversities on type 1 diabetes risk. The effects of specific childhood adversities on type 1 diabetes were estimated using proportional hazards models. Results: Accumulation of childhood adversities had a quantitatively small effect on type 1 diabetes risk among females [adjusted hazard ratio (HR) per adversity increase: 1.07; 95% confidence interval (CI): 1.02–1.11], but not among males (adjusted HR per adversity increase: 0.99; 95% CI: 0.97–1.03). Females exposed to extreme numbers (7+) of adversities had two times higher risk of type 1 diabetes compared with unexposed females (adjusted HR: 2.06; 95% CI: 1.10–3.86). Conclusions: In an unselected total population sample, we generally find no or negligible effects of childhood adversities on type 1 diabetes risk, which may be reassuring to persons with type 1 diabetes who are concerned that personal trauma contributed to their disease. There is a very small group of females exposed to a high degree of adversity who may have a higher risk of type 1 diabetes and this group needs further attention.